London Bridge New York City Ballet dancers visit Sadler's Wells - Simpson, Jane (Dance Books Ltd., Alton,Hampshire (UK), 2002)
New York City Ballet dancers in London. Movement pervades Ansanelli's body so completely that when she stops it's like watching water slowly coming to rest. PALABRAS CLAVE: New York City Ballet, Dances at a Gathering, Alexandra Ansanelli, Christopher Wheeldon, Polyphonia.